PERAN PEMIMPIN MA’HAD DALAM MENINGKATKAN KUALITAS PROSES BELAJAR MENGAJAR DI MA’HAD DARUL MA’RIF - Adnan Kamah; Afif Anshori; Nurul Hidayati Murtafiah (UNISAN JURNAL, 2022)
The Leader has the greatest incentive to raise the caliber of the teaching and learning process. The most important factor in how leaders should behave in accordance with the educational system is their job, which in this case is that of a manager in terms of resource management, planning, and organization. That involves resolving administrative issues and enhancing extracurricular program management as an administrator. The way in which Ma’had leaders can enhance the caliber of the teaching and learning process in Ma’had is how the problem is formulated in this thesis. What are the initiatives or strategies that Darul Patani needs to put into action to raise the caliber of the teaching and learning process and the educational system as a whole? The data for this study was gathered using qualitative approaches, including observation, interviews, and documentation. A triangulation form is used in the method of validating the data. Ma’had/Mudir Dreamers, Ustaz, Students, Parents, Administrative Personnel, and Alumni made up the informants. The study’s findings indicate that in order to enhance the standard of instruction at, educators must continue to work on their own personal development in accordance withThe more work put into the world of globalization and the educational system described in Ma’had’s vision, mission, and goals, the longer it takes to reach the objectives, both short-term and long-term. The study’s findings support the idea that Ma’had Dreamers play a crucial role in enhancing the effectiveness of the teaching and learning process there.